Artemis Fowl : the time paradox / 6. - Colfer, Eoin (Artemis Fowl, 2008)
Artemis's fairy friends help him travel back in time to find a cure for his mother's rare disease which can only be cured by the brain fluid of now-extinct African lemurs, and is shocked to discover that it was actually his younger self who was responsible for bringing about the animal's extinction.